The Effect of Diet Consisting of Grass and Tofu By Product Supplemented Soybean Hulls on Its Digestibilities and Milk Production of Anglo Nubian Does: Pengaruh Penambahan Kleci pada Campuran Pakan Rumput dan Ampas Tahu terhadap Kecernaan dan Produksi Susu Kambing Anglo Nubian - Akbarillah, Tris; Hidayat, Hidayat; Pratiwi, L.; Purnamasari, D.; Utama, E. Y.; Nurzaman, S. (BPFP Universitas Bengkulu, 2024)
This experiment was conducted to evaluate diet consiting of grass and tofu dregs supplemented soybean hulls on its digestibilities and milk production of Anglo Nubian does. Three heads of Anglo Nubian does, aging 17-18 month old, first parity, early lactation used as experimental animals. Latin square design was applied on this experiment with 3 treatments and 3 periods. The treatments were P0 ( 5 kg grass+ 6 kg tofu dregs+ 20 g mineral diluted on 20 g rice bran) as a control, P1 (P0+ 300 g wet soybean hulls), and P2 (P0 + 600 g wet soybean hulls). Data collected were analysed of variance, continued by least signifcant difference test. Variables measured were nutrition contens of feeds, feeds consumption: either grass, concentrates, or total consumption. The variables observed were the nutritional content of feed ingredients, nutrient consumption from forage and concentrates (tofu dregs and soybean hulls), and total nutrient consumption, as well as feed digestibility, and daily milk production. The experimental results showed that the average nutritional consumption of forage feed was not significantly different (P>0.05), the average nutritional consumption of concentrate feed was significantly different (P<0.05), increased by adding soybean hulls, but the total nutritional consumption of feed did not different (P>0.05). The average digestibility of feed nutrients was not significantly different (P>0.05), however the digestibility of crude fiber and nitrogen free extracts showed a decrease (P<0.05) with the addition of soybean hulls to the diet. The average daily milk production, P0 was 1699.29 ml/h/d, not significantly different (P>0.05) from P1, which was 1764.76 ml/h/d, but P2 milk production which was 1853.33 ml/h/d was significantly higher (P< 0.01) than P0 and P1. This research can be concluded that the addition of 600 g of wet soybean hulls to the diets on early lactation Anglo Nubian does may increase the average daily milk production